PERAN SISTEM INFORMASI KESEHATAN BERBASIS WEBSITE DALAM MENDUKUNG PENYELENGGARAAN PEMBANGUNAN KESEHATAN DI INDONESIA - Natasya Nazla Prasetyo; Endah Pravita Putri Aldia Pratama; Prasetio Hadi Pratama; Putri Aulia Rosmayani; Novita Dwi Istanti (Pusat Riset dan Inovasi Nasional, 2022)
Along with the development of the health service system, the government realizes the importance of data and information in the health sector to organize effective and efficient health efforts. Health information with precise, accurate and accountable data is needed because it is the main source for making health decisions. The purpose of this study is to determine the role of website-based health information systems in supporting the implementation of health development in Indonesia. This study uses the method of library studies (systematic review) with search engines used in the search for literature such as Google Scholar and Garuda with keywords Health Information Systems, websites and Health Development. The resulting articles were selected based on publications published between 2018 to 2022. The results showed the role of website-based health information systems in supporting the implementation of health development in Indonesia by paying attention to human resources, infrastructure and cost allocation. The conclusion of this study shows that SIK is part of the subsystem of Health Management and regulation that is able to produce adequate health policy, administration and information functions and is able to support the implementation of health development efforts in Indonesia.